Application of an Integrated Statistical Design for Optimization of Culture Condition for Ammonium Removal by Nitrosomonas europaea - yingling, Bao (Public Library of Science, 2013)

(untitled)
Statistical methodology was applied to the optimization of the ammonium oxidation by Nitrosomonas europaea for biomass concentration (C(B)), nitrite yield (Y(N)) and ammonium removal (R(A)). Initial screening by Plackett-Burman design was performed to select major variables out of nineteen factors, among which NH(4)Cl concentration (C(N)), trace element solution (TES), agitation speed (AS), and fermentation time (T) were found to have significant effects. Path of steepest ascent and response surface methodology was applied to optimize the levels of the selected factors. Finally, multi-objective optimization was used to obtain optimal condition by compromise of the three desirable objectives through a combination of weighted coefficient method coupled with entropy measurement methodology. These models enabled us to identify the optimum operation conditions (C(N) = 84.1 mM; TES = 0.74 ml; AS = 100 rpm and T = 78 h), under which C(B) = 3.386×10(8) cells/ml; Y(N) = 1.98 mg/mg and R(A) = 97.76% were simultaneously obtained. The optimized conditions were shown to be feasible through verification tests.